Regulation of parathyroid hormone gene expression by hypocalcemia, hypercalcemia, and vitamin D in the rat. - Naveh-Many, T (1990)
In vivo in the rat 1,25(OH)2D3 decreases and a low calcium increases PTH mRNA levels. We now report the effect of 3 and 8 wk of changes in dietary vitamin D and calcium on PTH mRNA levels. PTH mRNA levels were increased by 3 wk of calcium deficiency (five times), a vitamin D-deficient diet (two times), and combined deficiency (10 times), but not changed by high calcium. Vitamin D-deficient-diet rats' PTH mRNA did not decrease after a single large dose of 1,25(OH)2D3, but did decrease partially after repeated daily doses of 1,25(OH)2D3. Rats after a vitamin D-, calcium-deficient (-D-Ca) diet did not respond to changes in serum calcium at 1 h. Flow cytometry of isolated cells from parathyroid-thyroid tissue separated the smaller parathyroid from the larger thyroid cells and allowed an analysis of parathyroid cell number. In normal vitamin D/normal calcium (NDNCa) rats the parathyroid cells were 24.7 +/- 3.4% (n = 6) of the total cell number, whereas in -D-Ca rats they were 41.8 +/- 6.6% (n = 6) (P less than 0.05). That is, -D-Ca rats had 1.7 times the number of cells, whereas they had 10 times the amount of PTH mRNA, indicating the major contribution (6 times) of increased PTH gene expression per cell. Moreover, a calcium-deficient, more so than a vitamin D-deficient diet, amplifies the expression of the PTH gene, and vitamin D is necessary for an intact response of PTH mRNA to 1,25(OH)2D3 or calcium.